Liver enzyme profile and progression in association with thyroid autoimmunity in Graves' disease. Issue 4 (15th July 2019) - Hsieh, Albert; Adelstein, Stephen; McLennan, Susan V.; Williams, Paul F.; Chua, Elizabeth L.; Twigg, Stephen M.
Abstract: Objective: To investigate the associations of Graves' disease (GD) severity, autoimmunity and longitudinal liver enzyme changes with time in a cohort with well‐characterized GD. Design: Retrospective cohort study. Patients: Patients diagnosed with Graves' disease, treated at Royal Prince Alfred Hospital Sydney, Adult Thyroid Clinic from 2000 to 2012 inclusive. Measurements: Inclusion criteria were patients with a complete set of TSH, FT4, FT3, liver enzymes and TSH receptor antibody (TRAb) results prior to commencement of thionamide therapy. Results: Of the 146 patients who had complete results, 69 (47%) had at least one abnormal liver enzyme. Gamma glutamyltransferase (GGT) was most frequently abnormal (74%), followed by alanine aminotransferase (ALT) (57%), alkaline phosphatase (ALP) (39%) and then aspartate aminotransferase (AST) (29%). Subsequent to thyroid function normalization, 78% of the liver enzymes were normalized, 10% were persistently abnormal and 12% were lost to follow‐up. Circulating TRAb, FT3 and FT4 results were categorized into mild, moderate and severe elevations. At univariate regression analyses, TRAb, FT3 and FT4 levels were each significantly associated with abnormal liver enzyme profile. Multivariate regression including TRAB, FT3 and FT4 as independent variables demonstrated FT3 and FT4 were more strongly associated with abnormal liver profile than TRAb. However, the initial FT3 and FT4 levels were not associated with abnormal liver profile in the subgroup with persistently abnormal liver profile. Conclusion: Graves' disease is commonly associated with abnormal liver enzymes, and most commonly with abnormal levels of GGT, and that an abnormal liver enzyme profile is more directly linked to the degree of thyrotoxicosis than levels of TRAB. Abstract : Graves' disease is commonly associated with abnormal liver enzymes, and most commonly with abnormal levels of GGT, and that an abnormal liver enzyme profile is more directly linked to the degree of thyrotoxicosis than levels of TRAB.